Lower Digit Symbol Substitution Score in the Oldest Old is Related to Magnetization Transfer and Diffusion Tensor Imaging of the White Matter - Venkatraman, Vijay; Aizenstein, Howard J.; Newman, Anne B.; Yaffe, Kristine; Harris, Tamara; Kritchevsky, Stephen; Ayonayon, Hilsa; Rosano, Caterina (Frontiers in Aging Neuroscience, 2011)
Background: Slowing information processing is common among community-dwelling elderly and it predicts greater mortality and disability risk. Slowing information processing is related to brain macro-structural abnormalities. Specifically, greater global atrophy and greater small vessel disease of the white matter have been associated to slower processing speed. However, community-dwelling elderly with such macro-structural abnormalities can maintain processing speed. The roles of brain micro-structure for slow processing in very old adults living in the community is uncertain, as epidemiological studies relating these brain markers to cognition and in the context of other health characteristics are sparse. Hypothesis: Information processing is cross-sectionally associated with white matter micro-structure independent of overt macro-structural abnormalities and also independent of health related characteristics. Methods: Imaging indices of micro-structure (diffusion tensor imaging, DTI, and magnetization transfer imaging, MTI), macro-structure (white matter hyperintensities, gray matter volume), Digit Symbol Substitution Test (DSST) and health characteristics were measured in 272 elderly (mean age 83 years old, 43% men, 40% Black) living in the community. Results: The DTI- and MTI-indices of micro-structure from the normal appearing white matter and not from the normal appearing gray matter were associated with DSST score independent of white matter hyperintensities and gray matter volumes. Associations were also independent of age, race, gender, mini-mental score, systolic blood pressure, prevalent myocardial infarction. Interpretation: DTI and MTI indices of normal appearing white matter are indicators of information processing speed in this cohort of very old adults living in the community. Since processing slowing is a potent index of mortality and disability, these indices may serve as biomarkers in prevention or treatment trials of disability.